Kurikulum Sekolah Dasar sebagai Instrumen Pengembangan Kompetensi Peserta Didik - Ashari Usman (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The elementary school curriculum plays a strategic role in shaping the foundation of students' competencies as preparation for facing the next level of education and the challenges of life in the future. This study aims to examine the role of the elementary school curriculum as an instrument for developing student competencies through a literature study approach. The method used is a literature study with a qualitative descriptive approach, through analysis of various scientific sources in the form of national and international journal articles, academic books, and relevant educational policy documents. The results of the study indicate that the elementary school curriculum is designed to develop student competencies holistically, encompassing aspects of knowledge, skills, and attitudes. The curriculum also reflects a shift in the learning paradigm from teacher-centered to student-centered, which encourages active student involvement in the learning process. In addition, the role of teachers is a key factor in the success of the curriculum implementation, because the quality of learning is highly dependent on teachers' understanding and competence in translating the curriculum into learning practices. Other findings indicate that limited infrastructure and differences in school contexts affect the effectiveness of curriculum implementation, requiring flexibility and adaptation in its application. The elementary school curriculum also functions as a strategic instrument in strengthening character and 21st-century skills, such as critical thinking, creativity, collaboration, and communication. This study is expected to provide theoretical and practical contributions to curriculum development and serve as a reference for educators and policymakers in improving the quality of primary education.